Video-assisted thoracoscopic surgery lobectomy – early experience - Robert Šimon; Marián Kudláč; Jozef Belák (Videosurgery and Other Miniinvasive Techniques)
Introduction: Video-assisted thoracoscopic surgery (VATS) lobectomy is the anatomical resection of a whole lobe ofthe lung followed by removal of the lymph nodes from the mediastinum using a thoracoscope and an access incision(small thoracotomy ≤ 5 cm) without using the rib spreader. Aim: To present the early experience with VATS lobectomy. Material and methods: Five patients were treated surgically using the VATS technique of anatomical lung resection atthe 2nd Department of Surgery, Pavol Jozef Šafárik University, University Hospital of L. Pasteur, Košice, (Slovak Republic)within 12 months from 10.2008 to 10.2009. Lobectomy was performed in 4 patients and pneumonectomy in 1 patient. Results: The mean operating time was 120 min (range 80-170 min). Following lobectomy a drain was inserted into thepleural cavity in 4 cases, whereas there was no drainage after 1 pneumonectomy. Drains were removed 2-5 days afterthe surgery. Four patients suffered from lung carcinoma (1 squamous cell carcinoma, 3 adenocarcinomas); 1 patienthad chondroid hamartoma. Postoperative condition was good in all patients. There were no early complications andpatients were released home on the 6th postoperative day on average. Conclusions: The advantages of VATS lobectomy have been widely discussed. There is a consensus that in elderlypatients with non-small cell lung cancer VATS lobectomy accompanied by mediastinal lymphadenectomy reduces theincidence of complications after the surgery and patients recover faster.